2013
DOI: 10.1063/1.4831754
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic reconnection under anisotropic magnetohydrodynamic approximation

Abstract: We study the formation of slow-mode shocks in collisionless magnetic reconnection by using one-and two-dimensional collisionless MHD codes based on the double adiabatic approximation and the Landau closure model. We bridge the gap between the Petschek-type MHD reconnection model accompanied by a pair of slow shocks and the observational evidence of the rare occasion of in-situ slow shock observations.Our results showed that once magnetic reconnection takes place, a firehose-sense (p || > p ⊥ ) pressure anisotr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…It has been suggested that BBFs associated with an earthward moving plasma bubble can be generated by reconnection in the magnetotail (Chen & Wolf, ). Simulations of reconnection using double‐adiabatic magnetohydrodynamic codes (e.g., Hirabayashi & Hoshino, ), hybrid codes (e.g., Higashimori & Hoshino, ), and PIC codes (e.g., Liu, Drake, & Swisdak, ) have shown that reconnection can generate a fast‐moving plasma cloud (we refer it to as ejecta) with pressure anisotropy of P ⊥ / P || < 1. With such anisotropy, a system becomes firehose unstable when the condition of C f = 1–0.5 · ( β || – β ⊥ ) < 0 is satisfied, where β = 2 μ 0 P / B 2 .…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It has been suggested that BBFs associated with an earthward moving plasma bubble can be generated by reconnection in the magnetotail (Chen & Wolf, ). Simulations of reconnection using double‐adiabatic magnetohydrodynamic codes (e.g., Hirabayashi & Hoshino, ), hybrid codes (e.g., Higashimori & Hoshino, ), and PIC codes (e.g., Liu, Drake, & Swisdak, ) have shown that reconnection can generate a fast‐moving plasma cloud (we refer it to as ejecta) with pressure anisotropy of P ⊥ / P || < 1. With such anisotropy, a system becomes firehose unstable when the condition of C f = 1–0.5 · ( β || – β ⊥ ) < 0 is satisfied, where β = 2 μ 0 P / B 2 .…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In this paper, we have only discussed the linear stability of the streaming MHD instability for an isotropic pressure, i.e., p ∥ = p ⟂ ; however, under a collisionless reconnection, it is known that the anisotropy in pressure for p ∥ > p ⟂ can be generated [e.g., Hirabayashi and Hoshino, 2013]. In this situation, the firehose instability may couple with the streaming modes [Arzner and Scholer, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…The first probable agent for the fluctuations in the jet is ion temperature anisotropy in the boundary between the inflow and outflow regions, i.e., the plasma sheet boundary layer (PSBL). In weak guide‐field reconnection exhausts, it has been reported from both simulations [ Lin and Swift , ; Liu et al , ; Hirabayashi and Hoshino , ] and observations [ Hoshino et al , ] that the ratio T i ,∥ / T i ,⊥ becomes greater than unity and often exceeds the marginal limit of the fire‐hose instability (FHI) in the PSBL. ( T i ,∥ and T i ,⊥ are the ion temperatures parallel and perpendicular to the local magnetic field, respectively.)…”
Section: Introductionmentioning
confidence: 99%